IFORMATIONAL SYSTEM DYNAFLEET - Halaj, Dusan (Doprava a spoje, 2012)
This paper deals with functions and hardware requirements of information system Dynafleet, which is purposely determined for carriers. Individual functions of Dynafleet are determined for cost optimization.